A Psychological Analysis of the Tutoring Concept in Louis Cha’s Novel—— From the Perspective of Mental Health Tutoring - Yunzhui Ma (Forest Chemicals Review, 2022)
This paper investigates the special social form of martial arts world, which influences and shapes the individual behavior of characters in the martial arts world. Louis Cha (Jin Yong )’s achievements not only break through the conventional pattern of martial arts novels, but also break through the barriers of elegance and vulgarity . Their rich literary information storage provides many modern and contemporary literature researchers with the opportunity and possibility of multi-angle interpretation. A careful analysis of the connotations of Louis Cha’s works is not difficult to find that they focus on human growth. The growth of Louis Cha’s protagonists is a process of continuous tutoring. The different mental processes of the protagonists also reflect their psychological ups and downs in different periods of growth. Driven by the psychological motivation of integrating into the martial arts society, they contact different roles in rivers and rivers, make friends with different peer groups and experience different psychological processes. The psychological activities and behaviors of many people create the development trend of jianghu society. Conversely, the social trend of rivers and lakes also acts on the psychological activities of people in rivers and lakes. An in-depth study of the educational phenomena and psychological characteristics of the characters in Louis Cha’s novels can clearly demonstrate that the characteristics of the characters in Louis Cha’s works are highly consistent with some theories of pedagogy. Looking back at Louis Cha’s works, we can analyze that the words and deeds of many characters created by Louis Cha are excellent samples. In this sense, those works not only show some traditional virtues of chivalrous men, but also reflect some typical characteristics. Those chivalrous men’s growth is inseparable from appropriate tutoring. Although some characters encounter various mental health problems in their growth process, the reason why the heroes in Louis Cha’s works become heroes is inseparable. Louis Cha’s works tell the truth of mental health tutoring with the growth stories of his male protagonists. These mental health tutoring ideas take Confucian educational thought as the core, affirm diligent self-learning, emphasize tutoring students according to their aptitude, confirm tutoring as the foundation, and advocate that martial arts world tutoring must put moral tutoring first and cultivate morality.